Chemofiltration of eriochrome black T-zinc complex and determination by X-ray spectrometry - Vega, Mabel del Carmen (2011)
In the present work, a new methodology for zinc preconcentration and separation and its determination by X-ray spectrometry is proposed. The methodology is based on the formation of a complex using Eriochrome black T (1-naphtalensulfonic acid, 3-hidroxy-4-((1-hidroxy-2-naphtalenyl)azo)-7-nitro, monosodium salt), EBT, as complexing agent. Next, the complex is retained on a polyamide membrane by a chemofiltration process. The chemofiltrated material on the membrane constitutes a thin film, which minimizes or eliminates the interelemental effects when the instrumental detection is realized by X-ray fluorescence spectrometry. As the preconcentration method presented is based on the formation of a complex which will interact with the membrane during the chemofiltration, it was necessary first to establish the optimal conditions for the complex formation of Zn-EBT in aqueous medium and then to explore the optimal conditions for obtaining the thin film. The pH dependence of the metal ion chemofiltration on the membrane and other variables, such as contact time and retention capacity of the membrane, were also optimized. Chemofiltration step provided an enrichment factor of 30,000, improving considerably the instrumental detection limit, allowing the determination of trace zinc in environmental samples.